Hubungan Praktik Menyusui Dengan Pertumbuhan dan Perkembangan Anak Usia 1-3 Tahun - Ningsih, Sitti Rahmah; Faradilah, Andi; Rahim, Rosdianah (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Growth and development are two different processes that reflecting the change of humanbeing. Nutrition play an important role to affects child's growth and development. Breastfeeding in terms of breastfeeding practices must be considered by the mother to achieve successfullness of growth and development . Indicators for effective breastfeeding consist of a chin attached to the breast, a wide-open mouth, lower lip sticking out, and most of the areola, especially those below, enter the baby's mouth. The purpose of this study was to determine the relationship of breastfeeding practices with growth (nutritional status) and development (children growth screening) of children aged 1-3 years. The research design used in this study was observational with a cross sectional approach and sampling using purposive sampling techniques based on inclusion and exclusion criteria determined by the researcher. The study located in Puskemas Takalar, Puskesmas Jeneponto and Puskesmas Sudian with 200 children included as sample. Data was obtained by doing direct interview and antropometric measurement. The results of this study showed that there was no correlation between breastfeeding practices with nutritional status(p> 0.612). However there was a significant relationship between breastfeeding practices and the development of children aged (p <0.009). Although no significant relationship was found between breastfeeding practices and child growth in this study, there was a tendency for children who had normal growth were came the good breastfeeding practice group.. we concluded that there is a significant relationship between breastfeeding practices and the development of children aged 1-3 years. We encourage mother to practice a proper breastfeeding to let their children achieve optimum growth and development status.